Bone defect repair material for simulating complete hierarchical structure of bone unit and preparation method of bone defect repair material

By preparing collagen fiber laminated plates in bone defect repair materials and performing specific rotary stacking and mineralization treatment, the complete hierarchical structure of bone units is accurately simulated, solving the limitations of existing materials in terms of mechanical properties, biocompatibility and in vitro osteogenic induction properties, and achieving more efficient bone defect repair.

CN119607263APending Publication Date: 2025-03-14HOSPITAL OF STOMATOLOGY SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411825097.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing bone defect repair materials are difficult to accurately simulate the complete hierarchical structure of bone units, resulting in limitations in mechanical properties, biocompatibility and in vitro osteogenic induction properties.

Method used

By preparing collagen fiber laminated plates, the complete hierarchical structure of bone units is accurately simulated by using specific rotary stacking angles and mineralization treatments, forming bone defect repair materials with excellent mechanical properties and biocompatibility.

Benefits of technology

The mechanical properties of bone defect repair materials have been improved, biocompatibility improvements and in vitro osteogenesis-induced performance enhancement, which can more effectively repair a large range of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607263A_ABST
    Figure CN119607263A_ABST
Patent Text Reader

Abstract

The invention relates to a bone defect repair material for simulating a complete hierarchical structure of bone units and a preparation method of the bone defect repair material, and belongs to the technical field of biomedical materials. The method comprises the following steps: firstly, preparing single-layer collagenous fibers by utilizing animal decellularized collagen tissue slices; sequentially rotating and stacking the single-layer collagenous fibers to prepare a collagenous fiber composite plate; the method comprises the following steps: mineralizing a collagenous fiber composite plate by using a mineralizing solution, curling into a three-dimensional body, preparing a bionic bone unit material, arranging the bionic bone unit material into a shape required for repairing defects, pouring a collagen solution, freeze-drying, self-assembling, and then cross-linking and mineralizing to obtain the bone defect repairing material. According to the invention, by selecting the specific rotary stacking angle of the single-layer collagenous fiber, the bone defect repair material prepared from the obtained collagenous fiber composite plate has better mechanical properties. A collagenous fiber composite plate prepared by utilizing a slicing technology is combined with mineralization treatment, so that a complete hierarchical structure of a bone unit can be accurately simulated, and the biomimetic material for efficiently repairing a large-range bone defect is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a bone defect repair material simulating a complete hierarchical structure of bone units and a preparation method thereof. Background Art

[0002] Repairing large defects caused by tumors, trauma, and infection is a common problem and challenge in clinical work. Repair materials for large bone defects require not only good osteogenic properties, but also excellent mechanical strength. Autologous bone transplantation is considered the gold standard for repair, but its clinical application is limited due to its limited sources of autologous bone and the need to open up a second surgical area to damage the donor tissue. Allogeneic bone transplantation and xenogeneic bone transplantation have the problem of immune rejection and lack the conditions for widespread application. With the continuous improvement of medical level and material preparation technology, the emergence of new biomedical materials has provided a new way for the replacement and repair of large-area bone defects, and is expected to fundamentally improve the limitations of the above treatment methods. Natural cortical bone has super strong mechanical strength, which is caused by the large number of osteon structures in cortical bone. Simulating osteons has become a feasible method to construct bone repair materials with excellent mechanical strength. However, osteons have a complex and orderly hierarchical structure, including seven levels. Existing bone defect repair materials can only simulate and reconstruct part of the hierarchical structure of bone units to varying degrees, and are still unable to fully reproduce the hierarchical structure of bone units, which limits the performance of the prepared bone defect repair materials in various aspects. How to simulate the complete hierarchical structure of bone units is the key to constructing materials for repairing large-scale bone defects. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a bone defect repair material simulating a complete hierarchical structure of bone units with good mechanical properties, biocompatibility and in vitro osteogenic induction performance and a preparation method thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a method for preparing a bone defect repair material simulating a complete hierarchical structure of bone units, comprising the following steps:

[0006] S1. Slice the animal decellularized collagen tissue, wash and dry it to obtain a single layer of collagen fibers; rotate and stack the single layer of collagen fibers, with the rotation angle of adjacent single layers of collagen fibers being 0° to 179° (preferably, the angle is 30° to 90°; more preferably, the angle is 30° to 60°); pressurize and fix, and dry to obtain a collagen fiber composite plate;

[0007] S2, mineralizing the collagen fiber composite board using a mineralizing liquid to obtain a mineralized collagen fiber composite board;

[0008] S3, rolling the mineralized collagen fiber composite plate into a three-dimensional shape, and drying it to obtain a bionic bone unit material;

[0009] S4. Arrange the bionic bone unit material into the shape required for repairing the defect and perfuse the collagen solution, freeze-dry and immerse in an alkaline solution for self-assembly, repeat the steps of perfusion, freeze-drying and self-assembly to obtain a bone unit array material fully filled with collagen solution, cross-link, wash and mineralize the bone unit array material to obtain the bone defect repair material.

[0010] The present invention makes the bone defect repair material prepared by the collagen fiber composite plate have better mechanical properties by selecting a specific rotational stacking angle of a single layer of collagen fibers. At the same time, the collagen fibers used in the present invention retain the original micromorphology and composition of collagen as a constituent component of bone tissue, improve the tissue compatibility and mechanical properties of the repair material, and can be better applied to bone defect repair. The present invention combines the collagen fiber composite plate prepared by slicing technology with mineralization treatment, which can accurately simulate the complete hierarchical structure of bone units and prepare a bionic material that can efficiently repair large-scale cortical bone defects such as maxillofacial areas.

[0011] As a preferred embodiment of the preparation method of the present invention, in step S1, the animal includes mouse, cow, sheep, pig, dog or monkey.

[0012] As a preferred embodiment of the preparation method of the present invention, in step S1, the thickness of the single layer of collagen fibers is 2-200 μm.

[0013] In step S1 of the preparation method of the present invention, the decellularization can be performed using conventional decellularization methods.

[0014] As a preferred embodiment of the preparation method of the present invention, in step S1, the tissue includes skin connective tissue, tendon tissue, ligament tissue or bone tissue.

[0015] As a preferred embodiment of the preparation method of the present invention, in step S1, the slicing is performed by embedding the animal decellularized collagen tissue in an embedding agent and then cutting it into slices; the purpose of washing is to remove the embedding agent in the slices; the thickness of the slices is 2.5-1000 μm; preferably, the slices are cut into slices along the direction of the collagen fibers.

[0016] As a preferred embodiment of the preparation method of the present invention, the embedding agent includes OCT embedding agent, paraffin or agar.

[0017] As a preferred embodiment of the preparation method of the present invention, in step S1, the rotational stacking is co-directional rotational stacking.

[0018] As a preferred embodiment of the preparation method of the present invention, in step S1, the number of stacked layers is 2 to 100 layers.

[0019] As a preferred embodiment of the preparation method of the present invention, in step S1, the angle of rotation of adjacent single-layer collagen fibers is 30°. Under this condition, the prepared bone defect repair material has the best bending modulus and the best mechanical properties.

[0020] As a preferred embodiment of the preparation method of the present invention, in step S1, the drying temperature is 0-55°C.

[0021] As a preferred embodiment of the preparation method of the present invention, in step S2, the composition of the mineralization liquid is: water, carboxymethyl chitosan (CMCS) 0.1-40wt%, dipotassium hydrogen phosphate (K2HPO4) 0.1-40wt%, and calcium chloride (CaCl2) 0.1-40wt%; or, the composition is: 1mM~1.5mMTris buffer (pH 7), carboxymethyl chitosan (CMCS) 0.1-40wt%, dipotassium hydrogen phosphate (K2HPO4) 0.1-40wt%, and calcium chloride (CaCl2) 0.1-40wt%.

[0022] As a preferred embodiment of the preparation method of the present invention, in step S2, the composition of the mineralization solution is: 1mM~1.5mM Tris buffer (pH 7), carboxymethyl chitosan (CMCS) 0.1-40wt%, dipotassium hydrogen phosphate (K2HPO4) 0.1-40wt%, and calcium chloride (CaCl2) 0.1-40wt%.

[0023] As a preferred embodiment of the preparation method of the present invention, in step S2, the composition of the mineralization solution is: 1mM Tris buffer (pH 7), 10wt% carboxymethyl chitosan (CMCS), 33wt% dipotassium hydrogen phosphate (K2HPO4), and 26.4wt% calcium chloride (CaCl2).

[0024] As a preferred embodiment of the preparation method of the present invention, in step S2, the mineralization time is 3-20 days.

[0025] As a preferred embodiment of the preparation method of the present invention, in step S2, the mineralization time is 9 days.

[0026] As a preferred embodiment of the preparation method of the present invention, in step S3, the number of curled layers is 2 to 100; the solid body includes a cylinder, an ellipsoid, a cuboid, a cube or an irregular body.

[0027] As a preferred embodiment of the preparation method of the present invention, in step S3, the collagen solution is a hydrochloric acid solution of bovine Achilles tendon collagen, and the concentration of the collagen solution is 1-10 mg / ml; the alkaline solution is 0.1 mM NaOH solution; the cross-linking agent used for cross-linking is EDC / NHS solution; the concentrations of EDC and NHS in the EDC / NHS solution are both 2-20 mg / ml.

[0028] As a preferred embodiment of the preparation method of the present invention, in step S3, the mineralization is carried out using a mineralizing liquid, and the composition of the mineralizing liquid is: water, carboxymethyl chitosan (CMCS) 0.1-40wt%, dipotassium hydrogen phosphate (K2HPO4) 0.1-40wt%, and calcium chloride (CaCl2) 0.1-40wt%; or, the composition is: 1mM~1.5mM Tris buffer (pH 7), carboxymethyl chitosan (CMCS) 0.1-40wt%, dipotassium hydrogen phosphate (K2HPO4) 0.1-40wt%, and calcium chloride (CaCl2) 0.1-40wt%.

[0029] As a preferred embodiment of the preparation method of the present invention, the composition of the mineralization solution is: 1mM~1.5mM Tris buffer (pH 7), 0.1-40wt% carboxymethyl chitosan (CMCS), 0.1-40wt% dipotassium hydrogen phosphate (K2HPO4), and 0.1-40wt% calcium chloride (CaCl2).

[0030] As a preferred embodiment of the preparation method of the present invention, the composition of the mineralization solution is: 1mM Tris buffer (pH 7), 10wt% carboxymethyl chitosan (CMCS), 33wt% dipotassium hydrogen phosphate (K2HPO4), and 26.4wt% calcium chloride (CaCl2).

[0031] In a second aspect, the present invention provides a bone defect repair material prepared using the preparation method.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention makes the bone defect repair material prepared by the collagen fiber composite plate have better mechanical properties by selecting the specific rotational stacking angle of the single-layer collagen fiber. At the same time, the collagen fibers used in the present invention retain the original micromorphology and composition of collagen as a constituent component of bone tissue, improve the tissue compatibility and mechanical properties of the repair material, and can be better suitable for bone defect repair. The present invention combines the collagen fiber composite plate prepared by slicing technology with mineralization treatment, which can accurately simulate the complete hierarchical structure of bone units and effectively simulate the characteristics of cortical bone matrix. The bone defect repair material prepared by the present invention has good mechanical properties, biocompatibility and in vitro osteogenic induction properties, providing a new choice for therapeutic materials for bone defect repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the preparation process of the bone defect repair material in Example 1 of the present invention;

[0035] Figure 2 The electron microscope image of the cross section of the bone defect repair material and a single bone unit therein of Example 1 of the present invention, A represents the bone defect repair material, and B represents a single bone unit; the scale in the figure is 750um;

[0036] Figure 3 The cross section and stereogram of the bone defect repair material of Example 1 of the present invention are obtained by CT scanning, wherein A represents the cross section and B represents the stereogram; the scale in the figure is 1 mm;

[0037] Figure 4 The SEM image of the cross section of the bone defect repair material and a single bone unit therein of Example 1 of the present invention, wherein A represents a single bone unit and B represents the bone defect repair material;

[0038] Figure 5 The compression modulus test results of the bone defect repair materials prepared in Examples 1-3 and the comparative example in Test Example 1 of the present invention;

[0039] Figure 6 The bending modulus test results of the bone defect repair materials prepared in Examples 1-3 and the comparative example in Test Example 1 of the present invention;

[0040] Figure 7 The bone parameter results of the femoral defect area of ​​rats repaired with the bone defect repair materials prepared by Examples 1-3 and the comparative example in Test Example 2 of the present invention for 8 weeks; *: P<0.05, ns: P>0.05. DETAILED DESCRIPTION

[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0042] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0043] Example 1

[0044] The bovine Achilles tendon tissue block was decellularized according to the method for decellularization of tendon tissue described in the article "An engineered lamellar bone mimicking full-scale hierarchical architecture for bone regeneration" (DOI: 10.1016 / j.bioactmat.2023.03.024) to obtain a bovine decellularized collagen Achilles tendon block, which was embedded with an OCT embedding agent, and then sliced ​​in a direction parallel to the fiber using a slicer with a thickness of 10 μm. The sliced ​​bovine decellularized collagen Achilles tendon slices were washed in 75% ethanol and deionized water in turn, and the OCT embedding agent was removed to obtain a single layer of collagen fibers (collagen fiber membrane). In an aqueous environment, the single layer of collagen fibers was stacked in the same direction at 30° on a polytetrafluoroethylene plate, and each layer was fully pressed with another polytetrafluoroethylene plate after stacking to remove bubbles between the layers. After stacking 20 layers, the collagen fiber composite plate was dried at room temperature and collected for later use.

[0045] Preparation of mineralization solution: Prepare 1 mM Tris buffer (pH about 7) containing 10 wt % carboxymethyl chitosan, 33 wt % K2HPO4, and 26.4 wt % CaCl2 as the mineralization solution.

[0046] The collagen fiber composite plate was placed in the prepared mineralization solution and soaked for 9 days, and the solution was changed every 3 days to obtain the mineralized collagen fiber composite plate. The 4 layers of mineralized collagen fiber composite plate were curled into a cylinder with the needle as the axis, and the needle was removed after drying at room temperature to obtain the bionic bone unit material for standby use. The 7 bionic bone unit materials were arranged into a hexagon, and a 1mg / ml collagen solution (200mg of fully freeze-dried bovine Achilles tendon collagen fiber tissue was dissolved in 200ml of 1mol / L hydrochloric acid solution, and fully stirred and dissolved for standby use) was perfused into the gaps between the bionic bone unit materials, freeze-dried, and then soaked in a 0.1mM NaOH solution for self-assembly. Repeat the freeze-drying-self-assembly steps to finally obtain a bone unit array material fully filled with collagen; use EDC / NHS solution (4 mg of EDC and NHS are dissolved in 1 ml of double distilled water to obtain EDC / NHS solution) as a cross-linking solution to cross-link the bone unit array material, wash with water, and then mineralize the cross-linked bone unit array material using the mineralizing solution according to the aforementioned method to obtain a bone defect repair material (referred to as 30° BOA). The schematic diagram of the preparation process of the bone defect repair material is shown in the figure. Figure 1 shown.

[0047] The structure of the prepared bone defect repair material was observed using an electron microscope. The electron microscope image of the cross section of the bone defect repair material and a single bone unit therein is shown in FIG. Figure 2 As shown, A represents bone defect repair material and B represents a single bone unit.

[0048] The bone defect repair material prepared by CT scanning, the cross-section and stereogram of the bone defect repair material CT scanning are as follows Figure 3 As shown, A represents a cross section and B represents a stereogram.

[0049] The structure of the prepared bone defect repair material was observed using a scanning electron microscope (SEM). The SEM image of the cross section of the bone defect repair material and a single bone unit therein is shown in FIG. Figure 4 As shown, A represents a single bone unit and B represents bone defect repair material.

[0050] Example 2

[0051] The preparation method of the bone defect repair material (denoted as 45° BOA) in this embodiment is the same as that in Example 1, the only difference being that the stacking angle of the collagen fiber composite plate is different. In this embodiment, the single-layer collagen fibers are stacked in the same direction in sequence at 45° rotation on the polytetrafluoroethylene plate.

[0052] Example 3

[0053] The preparation method of the bone defect repair material (denoted as 60° BOA) in this embodiment is the same as that in Example 1, the only difference being that the stacking angle of the collagen fiber composite plate is different. In this embodiment, the single-layer collagen fibers are stacked in the same direction in sequence at 60° rotation on the polytetrafluoroethylene plate.

[0054] Comparative Example

[0055] The preparation method of the bone defect repair material in this comparative example (denoted as 90° BOA) is the same as that in Example 1, the only difference being that the stacking angle of the collagen fiber composite plate is different. In this example, the single-layer collagen fibers are stacked on the polytetrafluoroethylene plate in the same direction at 90° rotation.

[0056] Test Example 1

[0057] The mechanical properties of the bone defect repair materials prepared in Examples 1-3 and the comparative example were tested.

[0058] 1. Compression strength

[0059] The bone units of the prepared bone defect repair material were uniformly cut into samples with a length of 2 mm, and the diameter of each sample was measured and the cross-sectional area was calculated. A universal mechanical machine was used for compression experiments. The samples were placed between the upper and lower clamps and compressed at a uniform speed of 6 mm / min. The load was recorded and the compression modulus was statistically calculated. The stress-strain curve was drawn. There were 12 samples in each group.

[0060] The compression modulus test results of the bone units of the bone defect repair materials prepared in Examples 1-3 and Comparative Examples are as follows: Figure 5 As shown in the figure, the compression modulus of bone defect repair materials prepared from collagen fiber composite plates with different rotational stacking angles is different. There is no significant difference in the compression modulus of bone defect repair materials corresponding to rotational stacking angles of 45 degrees and 60 degrees, and both are lower than the compression modulus of bone defect repair materials corresponding to rotational stacking angles of 30 degrees and 90 degrees. The compression modulus of bone defect repair materials corresponding to a rotational stacking angle of 90 degrees is significantly higher than that of a rotational stacking angle of 30 degrees.

[0061] 2. Bending strength

[0062] The osteons of the prepared bone defect repair materials were fixed on a three-point bending fixture. Ten samples were set for each group of materials and pressurized uniformly at a rate of 1 mm / s. The bending modulus of each group of bionic osteons was calculated and the stress-strain curve was plotted.

[0063] The bending modulus test results of the bone units of the bone defect repair materials prepared in Examples 1-3 and Comparative Examples are as follows: Figure 6 As shown, the results show that the bending modulus of bone defect repair materials prepared by collagen fiber composite plates with different rotational stacking angles is different. The bending modulus of bone defect repair materials corresponding to the rotational stacking angles of 30 degrees, 45 degrees, and 60 degrees is significantly higher than that of the rotational stacking angle of 90 degrees. There is no significant difference between the bending moduli of bone defect repair materials corresponding to the rotational stacking angles of 45 degrees and 60 degrees, and both are less than the rotational stacking angle of 30 degrees. This shows that the mechanical properties of bone defect repair materials corresponding to the rotational stacking angles of 30 degrees, 45 degrees, and 60 degrees are better than those of the rotational stacking angle of 90 degrees, among which the mechanical properties of bone defect repair materials corresponding to the rotational stacking angle of 30 degrees are the best.

[0064] Test Example 2

[0065] A total of 64 lateral condylar critical bone defects were prepared in the bilateral femurs of 32 rabbits, and the rabbits were randomly divided into 7 groups according to different implant materials, including negative control group, mineralized collagen group, 90° bionic bone unit array group, 60° bionic bone unit array group, 45° bionic bone unit array group, 30° bionic bone unit array group, and positive control group, with 9 samples in each group. The skin of the surgical area of ​​the bilateral hind limbs of each rabbit was prepared, and the rabbit was fixed on the animal operating table in a supine position. Routine disinfection and draping were performed. The position of the lateral femoral condyle was determined on the lateral side of the femur and 1 cm above the knee joint. A longitudinal surgical incision of about 2.5 cm was made with the lateral femoral condyle as the center. The skin was cut open, and the subcutaneous tissue, muscle to periosteum were separated layer by layer to fully expose the rabbit femoral condyle, and the periosteum was peeled off. First, a 2mm diameter Kirschner wire was used to drill holes perpendicular to the bone surface to ensure that the center of the bone defect was 0.5-1.0cm away from the distal end of the femur. A circular bone drill was used perpendicular to the long axis of the bone shaft to prepare a critical bone defect in a cylindrical shape with a diameter of 6mm and a depth of 8mm. The defect was rinsed with saline to remove bone fragments and blood accumulation. The corresponding bone replacement material was implanted according to the experimental group, and the incision was sutured layer by layer. Samples were collected at 8 weeks after surgery.

[0066] NC negative control (no material is placed), MC mineralized collagen (1 mg / ml collagen solution, freeze-dried, soaked in alkaline solution, washed with water, collagen with similar array size. Cross-linked with the EDC / NHS solution of Example 1, washed with water, and mineralized with the mineralizing solution of Example 1), BOA (bone defect repair materials prepared in Examples 1-3 and Comparative Examples), PC positive control (placed with removed autologous bone slices)

[0067] The femoral defect of rats was repaired using the bone defect repair materials prepared in Examples 1-3 and the comparative example. After 8 weeks of repair, a three-dimensional reconstructed image was obtained by scanning with micro CT, and the HU value (grayscale value) of the femoral defect repair area was obtained and analyzed. The bone volume fraction (BV / TV) and bone density (BMD) were calculated.

[0068] The bone parameter results of the femoral defect area of ​​rats repaired with the bone defect repair materials prepared in Examples 1-3 and the comparative example after 8 weeks are as follows: Figure 7 As shown, *: P<0.05, ns: P>0.05. The results showed that the average bone density of the BOA group was close to that of the positive control group, and both were higher than those of the negative control group and the mineralized collagen group. This indicates that the bone defect repair material has a good in vivo osteogenesis effect.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a bone defect repair material simulating a complete hierarchical structure of bone units, characterized in that: The following steps are involved: S1. Slice the animal decellularized collagen tissue, wash and dry it to obtain a single layer of collagen fibers; rotate and stack the single layer of collagen fibers, with the rotation angle of adjacent single layers of collagen fibers being 0° to 179°, pressurize and fix, and dry to obtain a collagen fiber composite plate; S2, mineralizing the collagen fiber composite board using a mineralizing liquid to obtain a mineralized collagen fiber composite board; S3, rolling the mineralized collagen fiber composite plate into a three-dimensional shape, and drying it to obtain a bionic bone unit material; S4. Arrange the bionic bone unit material into the shape required for repairing the defect and infuse it with collagen solution. After freeze-drying, immerse it in an alkaline solution for self-assembly. Repeat the freeze-drying and self-assembly steps to obtain a bone unit array material fully filled with collagen solution. Cross-link, wash and mineralize the bone unit array material to obtain the bone defect repair material.

2. The preparation method according to claim 1, characterized in that In step S1, the animal includes mouse, cow, sheep, pig, dog or monkey; And / or, the tissue comprises skin connective tissue, tendon tissue, ligament tissue or bone tissue.

3. The preparation method according to claim 1, characterized in that: In step S1, the slicing is performed by embedding the animal decellularized collagen tissue in an embedding medium and then cutting it into slices; And / or, the slice has a thickness of 2.5-1000 μm.

4. The preparation method according to claim 1, characterized in that: In step S1, the rotation stacking is the same direction rotation stacking; And / or, the number of stacked layers is 2 to 100 layers.

5. The preparation method according to claim 1, characterized in that: In step S2, the composition of the mineralization solution is: water, 0.1-40wt% carboxymethyl chitosan, 0.1-40wt% dipotassium hydrogen phosphate, and 0.1-40wt% calcium chloride; or, the composition is: 1mM~1.5mM Tris buffer, 0.1-40wt% carboxymethyl chitosan, 0.1-40wt% dipotassium hydrogen phosphate, and 0.1-40wt% calcium chloride.

6. The preparation method according to claim 1, characterized in that: In step S3, the number of curling layers is 2 to 100; And / or, the solid includes a circle, an ellipse, a cuboid, a cube or an irregular body.

7. The preparation method according to claim 1, characterized in that: In step S4, the collagen solution is a hydrochloric acid solution of bovine Achilles tendon collagen, and the concentration of the collagen solution is 1-10 mg / ml; The alkaline solution is 0.1 mM NaOH solution; The cross-linking agent used in the cross-linking is EDC / NHS solution.

8. A bone defect repair material prepared by the preparation method according to any one of claims 1 to 7.